2017
DOI: 10.1007/s12070-017-1211-5
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal Endoscopic Optic Nerve Decompression in Post Traumatic Optic Neuropathy

Abstract: To quantify the successful outcome in patients following optic nerve decompression in post traumatic unilateral optic neuropathy in form of improvement in visual acuity. A prospective study was carried out over a period of 5 years (January 2011 to June 2016) at civil hospital Ahmedabad. Total 20 patients were selected with optic neuropathy including patients with direct and indirect trauma to unilateral optic nerve, not responding to conservative management, leading to optic neuropathy and subsequent impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 1 publication
3
14
0
1
Order By: Relevance
“…It is widely believed that the transcranial approach provides better surgical view and exposure, but in the meantime, it results in more complications in the form of brain retraction injuries. 17 The endoscopic surgery technique is also performed in the field of neurosurgery such as optic nerve decompression. The endoscopic technique offers many advantages, including decreased morbidity, preservation of olfaction, rapid recovery, and more acceptable cosmetic results without any external scars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely believed that the transcranial approach provides better surgical view and exposure, but in the meantime, it results in more complications in the form of brain retraction injuries. 17 The endoscopic surgery technique is also performed in the field of neurosurgery such as optic nerve decompression. The endoscopic technique offers many advantages, including decreased morbidity, preservation of olfaction, rapid recovery, and more acceptable cosmetic results without any external scars.…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of optic nerve decompression is to relieve the compression in the intracanalicular portion of the optic nerve. 10 Endoscopic optic nerve decompression (EOND) using a trans-ethmosphenoid approach is less invasive compared with the transcranial approach. Although EOND has been widely applied in the treatment of TON, its efficacy remains controversial, with no consensus about its appropriate indications and timing.…”
Section: Introductionmentioning
confidence: 99%
“…A number of advantages of approaching the base of the skull via endoscopic endonasal approach have been noted. 1 , 3 , 8 , 10 , 14 , 17) This technique is less invasive and shows excellent exposure to OC and orbital apex than classic transcranial approach.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Several authors who reported on optic nerve decompression surgery have presented the following indications for surgery: 1) History of traumatic face and head injury with and without OC injury; 23 33) 2) progressive loss of vision not associated with non-traumatic intraocular lesions; 14 23 33) 3) a lack of evidence of damage or avulsion to the intracranial portion of the optic nerve; 14 30) 4) Prolonged absolute latency or amplitude reduction in preoperative visual evoked potential (VEP) scan; 15 24) 5) failure to respond to steroid therapy; 6 14 16 23) and 6) the presence of bony fragments compressing the optic nerve or a hematoma near the optic nerve.…”
Section: Indications and Contraindications Of Surgerymentioning
confidence: 99%
“…Timely intervention could block the pathophysiological process and relieve nerve swelling and ischemia, possibly recovering the VA. Early intervention (within 3 days or even 7 days) with ETOCD or/and corticosteroid therapy has been proposed, and is regarded to yield a good prognosis (16,(35)(36)(37)(38). The efficiency rate in patients treated within 3 days was significantly higher than those in patients treated later than 7 days (63.6% vs. 35.7%) (36).…”
Section: A B C D E Fmentioning
confidence: 99%